Science, Technology and Mathematics (STM) Medium of Curbing Insecurity and Economics Depression in South-West Nigeria - Adeola.O. Odebode; Kamoru Abiodun SABITU; Motunrayo I. Adeyemi; Olufunso Caroline, Dele-Adisa (Peerian Journals Publishing, 2024)
This study will examine how science, technology, and mathematics (STM) can solve insecurity and economic problems in southwest Nigeria. The study employed a survey research design. The total population of this study consisted of 5,670 people, of which 3,789 were randomly selected across the five states in southwest Nigeria. The instruments used were a structured questionnaire titled Science, Technology and Mathematic Tool for Solving Insecurity and Economics Problems in South-West Nigeria Rating Scale (STMTSIEPRS) (r=0.85). Three research questions were formulated and tested. Data were analysed using Multiple Regression. The results revealed a significant primary influence of Science, Technology and Mathematics on Economic insecurity in South-West Nigeria with (R = .258 and a multiple R2 of .066). Also, it revealed the relative contribution of two dependent variables to the independent variables, expressed as beta weights, vis insecurity (beta equals .006, t= 5.178) and economic problems (beta equals .419,β = .419, 5 t = 5.086). It was therefore concluded that Mathematics, Science and Technology play a major role in the economic advancement of a community and as well can enhance strong security if adequately utilized. It was recommended that the Government fund researches on Science, Technology and Mathematics to end economic recession and insecurity.
Keywords: Economic depression; insecurity